The Electron Temperature and The Electron Density measurement by Optical Emission Spectroscopy in Laser Produced Aluminum Plasma in Air - Yaseen , Waleed Ibrahim (Iraqi Journal of Science, 2022)
In this work the Aluminum plasma in Air produced by Nd: YAG pulsed laser, (λ = 1064 nm, τ = 6 ns) has been studied with a repletion rate of 10 Hz. The laser interaction in Al target (99.99%) under air atmosphere generates plasma, which is produced at room temperature; with variation in the energy laser from 600-900 mJ. The electron temperature and the electron density have been determined by optical emission spectroscopy and by assuming a local thermodynamic equilibrium (LTE) of the emitting species. Finally the electron temperature was calculated by the Boltzmann plot from the relative intensities of spectral lines and electron density was calculated by the Stark-broadening of emission line.